Cathode materials for lithium ion battery containing yttrium borate, manufacturing method thereof and lithium ion battery including the same

KR103022762B1Active Publication Date: 2026-09-18IND ACADEMIC COOPERATION FOUND UNIV OF INCHEON
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
KR1020240147891
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2026-09-18
Estimated Expiration
2044-10-25

Smart Images

  • Figure 112024116975616-PAT00001_ABST
    Figure 112024116975616-PAT00001_ABST
Patent Text Reader

Abstract

According to one embodiment of the present invention, a cathode material for a lithium secondary battery is provided, characterized by comprising an NCM-based cathode active material and a yttrium borate (YBO3) additive.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a cathode material for a lithium secondary battery comprising yttrium borate, a method for manufacturing the same, and a lithium secondary battery comprising the same. Background Technology

[0002] With the increasing adoption of electric vehicles, the existing market for lithium-ion batteries (LIBs), a major power source, has expanded significantly over the past few years. LIBs, which were successfully commercialized as a major power source in 1991, have seen a rapid increase in demand in recent years due to efforts to reduce dependence on fossil fuels.

[0003] In particular, with the recent surge in the electric vehicle market, the demand for LIBs capable of extending driving range has increased exponentially, leading to continuous research on LIBs capable of providing high energy density to meet current requirements.

[0004] The energy density of LIBs is proportional to the cell capacity and potential, which are determined by the type of electrode material. Therefore, extensive research efforts are currently focused on developing advanced cathode materials capable of significantly improving the energy density of LIBs. Traditionally, 150mA hg with an average potential of 3.8V -1 Layered LiCoO2 (LCO), which exhibits a specific capacity, was the cathode material selected in conventional LIBs.

[0005] Due to recent developments, layered LiNi is characterized by partial substitution of Co and Ni in the layered structure. x Co y Mn zO2(NCM) cathode materials have been developed, which are noteworthy because the reversible oxidation / reduction of Ni is initiated at a lower electrochemical potential than that of Co, leading to a higher specific capacity, and thus the reversible oxidation / reduction of Ni can achieve a higher capacity than that of conventional LCO cathodes. Current research efforts are focused on developing NCM cathode materials with a Ni composition of 80% or more, which are considered next-generation cathode materials in consideration of the energy density of LIBs.

[0006] However, despite these advancements, the cycling behavior of NCM cathode materials is severely degraded due to inherent instability during cycling. In particular, Ni at the cathode interface during charging 4+ The formation of is due to chemical instability, where stable Ni has a higher tendency to accept electrons from the surroundings. 2+ It tends to decrease. At this stage, the electron-rich electrolyte is Ni 4+ It easily transfers electrons to the NCM interface and becomes unstable, causing the decomposition of the electrolyte.

[0007] These parasitic reactions at the interface lead to the accumulation of byproducts, resulting in Li at the interface. + It hinders delivery. In particular, since these parasitic reactions are primarily triggered in Ni-excess environments under high-temperature conditions, addressing the rapid decrease in retention rate is essential to ensuring the stable electrochemical performance of LIBs.

[0008] Over the past few years, there have been many attempts to mitigate undesirable interfacial reactions, such as using functional dopants or coating precursors that stabilize the structure of NCM cathode materials. In particular, surface modification using functional coating precursors is known as an efficient approach to stabilizing the interfacial properties of NCM cathode materials, as these coating precursors consist of artificial anode electrolyte intermediates (CEIs) that mitigate the continuous degradation of the electrolyte. For example, fluorinated inorganic materials such as AlF3, CaF2, and LiF are considered effective coating precursors for NCM cathode materials because they can reduce the surface area of ​​the NCM cathode material through a simple thermal modification process. Phosphate and oxide-based materials such as AlPO4, FePO4, B2O3, Al2O3, and ZrO2 are also considered efficient coating candidates because they provide excellent protection against unwanted reactions occurring at the interface.

[0009] These coating materials are generally composed of transition metals from the third period of the periodic table, and most of these well-known transition metals have already been investigated. Prior art literature

[0010] Republic of Korea Published Patent No. 10-2012-0099375 The problem to be solved

[0011] The present invention relates to a cathode material for a lithium secondary battery comprising yttrium borate, a method for manufacturing the same, and a lithium secondary battery comprising the same. means of solving the problem

[0012] In order to solve the above technical problem, according to one embodiment of the present invention, a cathode material for a lithium secondary battery is provided, characterized by comprising an NCM-based cathode active material and a yttrium borate (YBO3) additive.

[0013] The above yttrium borate (YBO3) additive is characterized by forming a coating layer on an NCM-based cathode active material.

[0014] The above coating layer is characterized by being formed in an island-type shape on the above NCM-based positive electrode active material.

[0015] The above yttrium borate (YBO3) additive is characterized by containing 1.0 to 3.0 mol% with respect to 100 mol% of the cathode material.

[0016] As the content of the above yttrium borate (YBO3) additive increases, the amount of residual Li2CO3 decreases, the change in internal pressure (ΔP) decreases, and the exothermic peak decreases, which is the characteristic feature.

[0017] The particle hardness of the cathode material increases as the content of the above yttrium borate (YBO3) additive increases.

[0018] The above NCM-based cathode active material is LiNi 0.83 Co 0.11 Mn 0.06 It is characterized by being O2.

[0019] According to another embodiment of the present invention, a method for manufacturing a cathode material for a lithium secondary battery is provided, comprising the steps of: mixing an NCM-based cathode active material and a yttrium borate (YBO3) additive; and heat-treating the mixture of the NCM-based cathode active material and the yttrium borate (YBO3) additive.

[0020] According to another embodiment of the present invention, a lithium secondary battery is provided comprising: a positive electrode; a negative electrode; and an electrolyte layer disposed between the positive electrode and the negative electrode, wherein the positive electrode comprises the positive electrode material described above.

[0021] On the anode surface above, Lix B y O z It is characterized by the formation of a base cathode-electrolyte interphase (CEI) layer.

[0022] It is characterized by a long-term cycling maintenance rate of 95.0% or higher. Effects of the invention

[0023] According to one embodiment of the present invention, YBO3 was used as an efficient precursor to stabilize the interfacial characteristics of an NCM anode.

[0024] YBO3 precursors well integrated into the NCM anode through heat treatment at low temperature can reduce internal pressure by promoting the thermal decomposition of Li2CO3, which can cause swelling.

[0025] In addition, incorporating YBO3 into the NCM cathode increases particle hardness, and based on the desirable bonding affinity of the NCM cathode material with oxygen, Li + Movement is facilitated.

[0026] The strong binding energy between yttrium and oxygen within the lattice can mitigate microcracks in cathode material particles through improved mechanical properties and minimize the reduction in capacity caused by the new coating layer of the cathode material.

[0027] In addition, boron can form an ion-conducting boron-based cathode-electrolyte intermediate phase by removing residual lithium carbonate from nickel-rich cathode materials through thermal decomposition.

[0028] According to electrochemical performance, the boron-functionalized anode shows an improved lifespan (95.5%) compared to the pure anode (83.8%) due to the yttrium borate hybrid anode-electrolyte intermediate phase, which effectively prevents microcracking of the nickel-rich anode material and subsequent electrolyte degradation during cycling.

[0029] According to additional morphological analysis (cross-section) performed using SEM and TEM, the 1.0 YBO3 anode material had less deformation, and as a result, the interfacial resistance caused by microcracks in the NCM anode material can be significantly reduced. Brief explanation of the drawing

[0030] Figure 1 is a schematic diagram of the effect of the YBO3 coating layer on an NCM anode. Figure 2 shows (a) a pure NCM cathode material and (b) a 1.0 YBO3 SEM image, (c) a pure NCM cathode material and (d) a TEM image of 1.0 YBO3, (e) an XRD pattern of a pure NCM cathode material and (f) 1.0 YBO3, and (g) B 1s and (h) Y 3d XPS spectra of 1.0 YBO3. Figure 3 shows (a) a quantitative graph of residual lithium carbonate of pure NCM cathode materials, 1.0 YBO3, 2.0 YBO3, and 3.0 YBO3, (b) internal pressure of pure NCM cathode materials, 1.0 YBO3, 2.0 YBO3, and 3.0 YBO3 during the charging stage, (c) DSC curves of pure NCM cathode materials, 1.0 YBO3, 2.0 YBO3, and 3.0 YBO3, and (d) a graph of particle hardness of pure NCM cathode materials, 1.0 YBO3, 2.0 YBO3, and 3.0 YBO3. Figure 4 shows (a) the CV curve of a pure NCM anode and (b) 1.0 YBO3, (c) the GITT profile of a pure NCM anode and 1.0 YBO3, and (d) the Arrhenius plot and calculated activation energy graph of a pure NCM anode and (e) 1.0 YBO3. Figure 5 shows (a) the potential profile and (b) the cycling performance of a pure NCM anode and 1.0 YBO3 at 25°C, (c) the dQ dV of the pure NCM anode and 1.0 YBO3, and (d) the dQ dV of the pure NCM anode and 1.0 YBO3. -1Plot, (e) potential profile of pure NCM anode and 1.0 YBO3 at 45°C and (f) cycling performance, (g) potential profile of pure NCM anode and 1.0 YBO3 for evaluating rate performance and (h) specific capacity graph of the anodes at each C-rate at 25°C. Figure 6 shows the SEM image of the recovered (a) pure NCM anode and (b) 1.0 YBO3, the TEM image and FFT pattern of the recovered (c) pure NCM anode and (d) 1.0 YBO3, the XRD pattern of the recovered (e) pure NCM anode and (f) 1.0 YBO3, the EIS spectra of the pure NCM anode and 1.0 YBO3 after (g) formation and (h) cycle, and the F 1s depth profiling XPS spectra of the recovered (i) pure NCM anode and (j) 1.0 YBO3. Specific details for implementing the invention

[0031] The above objects, other objects, features, and advantages of the present invention will be easily understood through the following preferred embodiments associated with the accompanying materials. However, the present invention is not limited to the embodiments described herein and may be embodied in other forms. Rather, the embodiments introduced herein are provided to ensure that the disclosed content is thorough and complete and that the spirit of the invention is sufficiently conveyed to a person skilled in the art.

[0032] In this specification, terms such as “comprising” or “having” are intended to specify the existence of the features, numbers, steps, actions, components, parts, or combinations thereof described in the specification, and should not be understood as precluding the existence or addition of one or more other features, numbers, steps, actions, components, parts, or combinations thereof.

[0033] Unless otherwise specified, all numbers, values, and / or expressions representing ingredients and reaction conditions used herein shall be understood to be modified by the term “approximately” in all cases, as these numbers are essentially approximations reflecting the various uncertainties of measurement that occur in obtaining these values ​​among others. Furthermore, where numerical ranges are disclosed herein, such ranges are continuous and, unless otherwise indicated, include all values ​​from the minimum value of such range to the maximum value including the maximum value. Moreover, where such ranges refer to integers, they include all integers from the minimum value to the maximum value including the maximum value, unless otherwise indicated.

[0035] In the present invention, the interfacial instability inherent in existing NCM cathode materials due to surface functionalization was resolved through the simultaneous embedding of yttrium (Y) and boron (B) elements by heat treatment (Fig. 1).

[0036] The simple heat treatment process of YBO3 involves Y being an oxygen atom (702.9 kJ mol -1 Because it exhibits high binding energy, it is possible to provide a Ni-rich NCM cathode material containing Y and B, and this desirable binding performance can increase the mechanical durability of the NCM cathode material.

[0037] In addition, the high binding energy with oxygen atoms is due to the lattice oxygen and the Li occupying the Li slab. + Since it can reduce ion interactions between them, Li during cycling + You can move it more easily.

[0038] Meanwhile, element B is residual Li + Li through reaction with species x B y O z It is possible to generate a base anode-electrolyte intermediate (CEI) layer, which reduces electrolyte interfacial decomposition and residual Li at the interface+ It plays an important role in reducing. Also, Li x B y O z Integrating a base CEI layer allows Li at the interface through an ion hopping mechanism + Because it promotes movement, it can suppress a rapid decrease in volume when the CEI layer is embedded.

[0039] Based on these considerations, Y and B functionalized NCM cathode materials could be conveniently obtained by systematically explaining the individual roles of Y and B using post-hoc analysis.

[0041] According to one embodiment of the present invention, a cathode material for a lithium secondary battery is provided, characterized by comprising an NCM-based cathode active material and a yttrium borate (YBO3) additive.

[0042] The above yttrium borate (YBO3) additive is characterized by forming a coating layer on an NCM-based cathode active material.

[0043] The above coating layer is characterized by being formed in an island-type shape on the above NCM-based positive electrode active material.

[0044] The above yttrium borate (YBO3) additive is characterized by containing 1.0 to 3.0 mol% with respect to 100 mol% of the cathode material.

[0045] As the content of the above yttrium borate (YBO3) additive increases, the amount of residual Li2CO3 decreases, the change in internal pressure (ΔP) decreases, and the exothermic peak decreases, which is the characteristic feature.

[0046] The particle hardness of the cathode material increases as the content of the above yttrium borate (YBO3) additive increases.

[0047] The above NCM-based cathode active material is LiNi 0.83 Co 0.11 Mn 0.06 It is characterized by being O2.

[0048] According to another embodiment of the present invention, a method for manufacturing a cathode material for a lithium secondary battery is provided, comprising the steps of: mixing an NCM-based cathode active material and a yttrium borate (YBO3) additive; and heat-treating the mixture of the NCM-based cathode active material and the yttrium borate (YBO3) additive.

[0049] The above yttrium borate (YBO3) additive is characterized by containing 1.0 to 3.0 mol% with respect to 100 mol% of the cathode material.

[0050] As the content of the above yttrium borate (YBO3) additive increases, the amount of residual Li2CO3 decreases, the change in internal pressure (ΔP) decreases, and the exothermic peak decreases, which is the characteristic feature.

[0051] The particle hardness of the cathode material increases as the content of the above yttrium borate (YBO3) additive increases.

[0052] According to another embodiment of the present invention, a lithium secondary battery is provided comprising: a positive electrode; a negative electrode; and an electrolyte layer disposed between the positive electrode and the negative electrode, wherein the positive electrode comprises the positive electrode material described above.

[0053] The above anode is LiNi 0.83 Co 0.11 Mn 0.06 It is characterized by including an O2 positive electrode active material.

[0054] On the anode surface above, Li x B y O zIt is characterized by the formation of a base cathode-electrolyte interphase (CEI) layer.

[0055] The above lithium secondary battery is characterized by exhibiting a long-term cycling retention rate of 95.0% or higher, and a cycling performance.

[0057] The present invention will be explained in more detail below through examples. However, these examples are intended only to aid in understanding the invention and do not limit the scope of the invention in any way.

[0059] Experimental Example

[0060] In the case of YBO3-coated NCM cathode material, 5.0g of NCM cathode material (LiNi 0.83 Co 0.11 Mn 0.06 O2, COSMO AM&T) and 0.05 g of yttrium borate (YBO3, Aldrich) were mixed using mortar for 15 minutes. The mixture was heated at O2 for 10 ℃ min -1 The mixture was heated to 350°C at a rate and maintained for 5 hours. After heating, the mixture was cooled to room temperature. The surface of the NCM anode material was observed using a scanning electron microscope (SEM; JSM IT-800, JEOL) and a field emission transmission electron microscope (FE-TEM; FEI Talos F200X, Thermo Fisher Scientific).

[0061] The lattice structure of the cathode material was described using X-ray diffraction (XRD; Empyrean, PANalytical), and the chemical composition of the cathode material was detected by X-ray photoelectron spectroscopy (XPS; K-Alpha, Thermo Fisher Scientific). Lithium carbonate remaining in the cathode was sampled with 0.1N nitric acid (HNO3, Daejeong) and quantified using a titrator (848 Titrino Plus, Metrom). The thermal behavior of the cathode was measured at a scan rate of 5 °C min -1The temperature was monitored from room temperature to 250°C using a differential scanning calorimeter (DSC, DSC N-650, Shinko). The grain hardness of the anode material was inspected using a microindenter (MCT-W500E, Shimadzu).

[0062] For electrochemical measurements, 1.8 g of NCM cathode material, poly(vinylidene fluoride) (Kureha), and Super-C (C-NERGY, 0.1 g) were dispersed in 1.6 mL of N-methylpyrrolidone (Ashland). The cathode slurry was then cast onto a current collector, and the resulting NCM cathode was dried. The average loading density of the cathode was 9.8 mg cm⁻³. -2 ...was. To observe changes in the internal pressure of the cell during charging, a cell equipped with a pressure sensor was assembled with an NCM anode (working electrode), a Li cathode (counter and reference electrode), a separator, and an electrolyte (1M lithium hexafluorophosphate (LiPF6) and ethylene carbonate (EC):ethylmethyl carbonate (EMC) in a 1:2 (v / v) ratio, as an assimilation electrolyte). The cell had a potential of 4.3V (Li / Li + It was charged until it increased to (compared to), and the internal pressure was recorded as functioning in real time at 45℃.

[0063] For cyclic voltammetry (CV) testing, use a potentiostat (VSP, Biologic) at 0.1 mV s⁻¹ -1 At a scan rate of 3.0V to 4.5V (Li / Li + The cells were scanned up to (comparison). The galvanostatic intermittent titration technique (GITT) was performed using a battery cycler (CT2001A, Land) from 3.0 to 4.5 V (Li / Li + It was used at a rate of 0.1C at 10-minute intervals (comparison), and the activation energy of the NCM anode was calculated using the Arrhenius equation:

[0064] k=Ae - E a / RT

[0065] Here, A is the factor before the exponent (collision frequency)(s -1 ), Ea is the activation energy (kJ mol -1 ), R is the general gas constant (8.314 J mol -1 K -1 ), T is the temperature (K).

[0066] For electrochemical cycling, cycle the cell for two cycles at a rate of 0.1C and at room temperature 3.0–4.3V (Li / Li + The speed was increased to 1.0C for 120 cycles (comparison). Speed ​​performance was verified by changing the C-rate from 0.1C to 2.0C at room temperature.

[0067] SEM and TEM analysis of the surface of the recovered NCM anode and electrochemical impedance spectroscopy (EIS) of the NCM anode were performed using cells charged from 1 MHz to 1 m Hz with an amplitude of 10 mV, along with structural changes measured by XRD (Smartlab, Rigaku). Changes in the chemical composition of the NCM anode after cycling were confirmed using XPS.

[0069] Experimental results

[0070] When YBO3 is used as a coating precursor, an island-type layer is formed on the NCM anode (Figs. 2a and 2b), and B and Y are clearly visible in the EDS image, indicating that a CEI layer composed of B and Y is well developed after the heating process.

[0071] TEM images show the uncoated surface of the pure NCM anode, whereas a distinct 3 nm thick layer is present on the YBO3-coated NCM anode (Figs. 2c and 2d). Despite the presence of this new layer, only minor changes in structural parameters were observed in the XRD patterns (Figs. 2e and 2f), and all NCM anodes showed I greater than 1.20 (003) / I (104)The ratio indicates that the YBO3-coated NCM anode maintained stable structural characteristics.

[0072] As characterized by XPS, the CEI layer derived from YBO3 consists of intrinsic B and Y functional groups (Figs. 2g and 2h). In the B 1s spectrum, BO and Li3BO3 peaks were observed at 192.6 eV and 192.1 eV, respectively. In the Y 3d spectrum as well, YBO3 peaks were observed at 158.15 eV and 160.2 eV, indicating that while some of the YBO3 is embedded within the NCM anode itself, some of the YBO3 is contained within the Li remaining in the NCM anode. + Indicates that there was an additional reaction with the species.

[0073] Quantifying the residual Li2CO3 of the NCM anode after coating, B and Li + The reactivity of the liver was confirmed (Fig. 3a). The pure NCM cathode material showed 2323.1 ppm of Li2CO3. In contrast, the YBO3-treated NCM cathode material showed a decrease in the amount of Li2CO3 in proportion to the YBO3 composition (1.0 YBO3: 2100.6 ppm, 2.0 YBO3: 2053.9 ppm, 3.0 YBO3: 1960.5 ppm).

[0074] This indicates that YBO3 can thermally react with Li2CO3 to generate Li3BO3 as part of the CEI composition (Fig. 3b). XRD analysis of the solid product obtained from the heat treatment of YBO3 and Li2CO3 revealed a Li3BO3 peak, indicating reactivity between YBO3 and Li2CO3. In particular, the Li2CO3 component decomposes into a gaseous component during cycling, causing swelling behavior in the LIB. Therefore, lowering the concentration of Li2CO3 using a YBO3 precursor can reduce internal pressure and improve safety performance. To verify this hypothesis, the internal pressure of the NCM cathode material was checked (Fig. 3b).

[0075] When the cell was charged with a pure NCM cathode, the change in internal pressure (ΔP) at the end of charging increased to 13.2 kPa. On the other hand, the YBO3-coated NCM cathode showed a smaller increase in ΔP (1.0 YBO3: 11.3 kPa, 2.0 YBO3: 10.2 kPa, 3.0 YBO3: 9.6 kPa) because Li2CO3 disappeared due to reaction with YBO3.

[0076] Additional DSC analysis revealed that YBO3 increased structural stability (Fig. 3c). Specifically, the pure NCM anode produced 17.2 J g at 207.1°C. -1 It showed an exothermic peak. On the other hand, the YBO3-coated NCM anode showed a delayed exothermic peak with a smaller amount of heat generation (1.0 YBO3: 16.7 J g -1 , 2.0 YBO3:15.5 J g -1 , 3.0 YBO3:14.9 J g -1 These observed exothermic peaks correspond to the thermal decomposition of the delithiated NCM anode due to layer structure deformation. Therefore, these DSC results indicate that the YBO3 precursor interacts with oxygen near the NCM anode surface, which can enhance thermal stability.

[0077] The grain hardness of the NCM cathode material was determined through indentation tests to evaluate the effect of YBO3 on mechanical performance (Fig. 3d). The pure NCM cathode material provided a grain hardness of 143.4 MPa, while the grain hardness of the YBO3-coated NCM cathode material increased in proportion to the amount of YBO3 (1.0 YBO3: 161.2 MPa, 2.0 YBO3: 178.8 MPa, 3.0 YBO3: 195.0 MPa). Grain hardness is correlated with the degree of deformation of the NCM cathode material, as lower grain hardness accelerates microcracks, thereby further promoting electrolyte decomposition during cycling. These observations indicate that unwanted interfacial reactions are well suppressed in the YBO3-coated NCM cathode material by improving mechanical properties, which can lead to improved retention behavior.

[0078] CV tests described the reversible behavior of the NCM cathode material to evaluate electrochemical compatibility (Figs. 4a and 4b).

[0079] Pure NCM and 1.0 YBO3 exhibited reversible oxidation / reduction behavior: 1.0 YBO3 showed 3.95 V (Li / Li) similar to that of pure NCM. + The first delithiation peak was observed at (3.99V, Li / Li) + (Comparison). In particular, 1.0 YBO3 is approximately 3.82 V (Li / Li) which is not observed in pure NCM. + It showed a shoulder peak (compared to), which means that a lower overvoltage occurred at 1.0 YBO3.

[0080] To clarify this behavior, Li + The diffusion coefficient (D Li+ ) was determined by GITT (Fig. 4c). 1.0 YBO3 is similar to pure NCM in the general potential range D Li+ It exhibited behavior, and in particular, 1.0 YBO3 was pure NCM (1.16 x 10⁻⁶ at filling) -8 cm 2 s -1 , 1.07 x 10 when discharged -8 cm 2 s -1 Average D, slightly increased compared to ) Li+ Provided a value (1.72 x 10 when charging) -8 cm 2 s -1 , 1.39 x 10 when discharged -8 cm 2 s -1 ).

[0081] Further comparative studies to estimate the activation energy of each NCM anode (calculation of Arrhenius plots considering resistance and temperature) supported the above explanation (Figs. 4d and 4e).

[0082] The activation energy of a pure NCM anode is 14.55 kJ mol -1 It was estimated, but 1.0 YBO3 is 13.54 kJ mol -1 It exhibited a reduced activation energy. In particular, when NCM cathode materials are coated with a coating precursor, the specific capacity generally decreases because a portion of the active surface is covered by the precursor, resulting in lower electrochemical activity during cycling. However, since the YBO3 coating precursor lowers the lithium carbonate content while the trade-off effects frequently occurring in precursor-coated cathode materials are well controlled due to the desirable binding affinity with oxygen near the surface of the NCM cathode material, Li + It can facilitate movement.

[0083] In terms of electrochemical performance, pure NCM and 1.0 YBO3 exhibited typical charge / discharge curves during the first cycle, but 1.0 YBO3 was compared to pure NCM (198.2 mA hg -1 Slightly higher specific discharge capacity than ) (201.9 mA hg -1 ) provided (Fig. 5a).

[0084] In the retention profile, the pure NCM anode retained a rate of 83.8% (151.6 mA hg) after 120 cycles. -1 It showed continuous fading behavior, such as decreasing to (Fig. 5b). On the other hand, 1.0 YBO3 showed stable cycling behavior after 120 cycles (95.5%).

[0085] dQ dV -1 In profile analysis, pure NCM and 1.0 YBO3 showed similar potential dQ dV for up to 90 cycles. -1 Curves were observed (Figs. 5c and 5d). However, significant changes occurred in the H2–H3 phase after 120 cycles. While the peak corresponding to the H2–H3 phase in pure NCM shifted significantly after 120 cycles, 1.0 YBO3 maintained a stable H2–H3 phase peak, indicating that there was little structural deformation after 120 cycles.

[0086] Further confirmation of the effect of the YBO3-based CEI layer is high potential (4.5V vs. Li / Li + It was obtained through high-temperature electrochemical cycling in (Figs. 5e and 5f). Although all samples were shown to gradually fade under harsh test conditions, 1.0 YBO3 maintained an improved retention rate (74.2%) compared to pure NCM (57.7%), demonstrating the effect of incorporating the YBO3 precursor in suppressing unwanted interfacial reactions.

[0087] In rate performance tests, the 1.0 YBO3 anode provided increased specific capacity compared to pure NCM anodes across all C-rate ranges (Figs. 5g and 5h).

[0088] The cycled NCM anodes were analyzed by SEM (Figs. 6a and 6b). In pure NCM, degradation adducts completely covered the surface of the NCM anode with extensive microcracking, implying that unwanted reactions were severely accelerated. In contrast, these unwanted behaviors were less pronounced in the recovered 1.0 YBO3. Macroscopic cross-sectional images of the anodes also showed that the secondary particles of the 1.0 YBO3 anode were well maintained even after cycling, whereas the recovered pure NCM exhibited numerous internal cracks due to deformation caused by microcracking. These results indicate that the CEI layer derived from YBO3 sufficiently mitigated the anisotropic shrinkage and expansion of the NCM anode based on improved mechanical properties, thereby significantly reducing mechanical stress during cycling.

[0089] Additional TEM analysis supported that 1.0 YBO3 maintained structural stability compared to pure NCM after cycling (Figs. 6c and 6d). Most parts of the cycled 1.0 YBO3 were composed of a layered structure in the TEM images, indicating that the layered structure was well maintained even after cycling.

[0090] In contrast, significant rock salt structures were observed in the TEM images of the cycled pure NCM, indicating that more structural deformation occurred in the pure NCM, consistent with the previously mentioned analysis. Further XRD analysis of the recovered NCM anodes confirmed the effect of the YBO3-derived CEI layer (Figures 6e and 6f). The distance between the (018) plane and the (110) plane in the pure NCM and 1.0 YBO3 anodes was 0.59° and 0.80°, respectively. In particular, as deformation of the layered anode is promoted, the distance between the (018) plane and the (110) plane narrows, indicating lower structural deformation in 1.0 YBO3.

[0091] Consistent electrochemical behavior was also observed in the internal resistance analysis (Figs. 6g and 6h). After the formation step, pure NCM and 1.0 YBO3 exhibited similar R CT and R CEI While showing resistance (pure NCM: R CT In the case of 21.24 Ω, R CEI In the case of 14.97 Ω, 1.0 YBO3: R CT In the case of 16.37 Ω, R CEI In the case of 12.52 Ω), a significant difference was observed after cycling, specifically, 1.0 YBO3 still had a similar resistance (R CT In the case of 229.5 Ω, R CEI In the case of , it showed 19.26 Ω), but in the case of the pure NCM anode, unwanted reactions were not well suppressed, so the internal resistance increased significantly after cycling (R CT In the case of 265.8 Ω, R CEI In the case of 63.2 Ω).

[0092] Therefore, the degree of failure of the NCM cathode was analyzed by analyzing the recovered cathode using XPS. The F 1s spectra (Figs. 6i and 6j) show that Li in the pure NCM cathode is greater than in the 1.0 YBO3 cathode. x PF y (688.2 eV), Li x PF yO z The concentrations of decomposed adducts such as (686.8 eV) and LiF (685.8 eV) were found to be higher, and similar behavior was observed in the etched F 1s spectrum, indicating that much higher electrolyte decomposition occurred in the pure NCM anode, whereas, in contrast, this parasitic reaction was suppressed in the 1.0 YBO3 anode.

[0093] In the present invention, YBO3 was used as an efficient precursor to stabilize the interfacial characteristics of an NCM anode.

[0094] YBO3 precursors well integrated into NCM cathodes through low-temperature heat treatment can reduce internal pressure by promoting the thermal decomposition of Li2CO3, which can induce swelling. Furthermore, the integration of YBO3 into NCM cathodes increases particle hardness, and based on the desirable bonding affinity of the NCM cathode material with oxygen, Li + Movement is facilitated.

[0095] In terms of cycling performance, 1.0 YBO3 showed improvement at ambient temperature and a long-term cycling retention rate (95.5%), whereas pure NCM gradually faded after 120 cycles (83.8%).

[0096] According to additional morphological analysis (cross-section) performed using SEM and TEM, the 1.0 YBO3 anode material had less deformation, and as a result, the interfacial resistance caused by microcracks in the NCM anode material was significantly reduced.

[0098] The present invention described above is not limited to the aforementioned embodiments, as various substitutions and modifications are possible within the scope of the technical concept of the present invention without departing from the technical spirit of the present invention for those skilled in the art to which the present invention belongs.

Claims

Claim 1 A cathode material for a lithium secondary battery comprising an NCM-based cathode active material and a yttrium borate (YBO3) additive, wherein the yttrium borate (YBO3) additive comprises 1.0 to 3.0 mol% with respect to 100 mol% of the cathode material, and is characterized in that the particle hardness of the cathode material increases as the content of the yttrium borate (YBO3) additive increases. Claim 2 A cathode material for a lithium secondary battery according to claim 1, characterized in that the yttrium borate (YBO3) additive forms a coating layer on an NCM-based cathode active material. Claim 3 A cathode material for a lithium secondary battery according to claim 2, characterized in that the coating layer is formed in an island-type shape on the NCM-based cathode active material. Claim 4 delete Claim 5 A cathode material for a lithium secondary battery according to claim 1, characterized in that as the content of the yttrium borate (YBO3) additive increases, the amount of residual Li2CO3 decreases, the change in internal pressure (ΔP) decreases, and the exothermic peak decreases. Claim 6 delete Claim 7 In claim 1, the NCM-based cathode active material is LiNi 0.83 Co 0.11 Mn 0.06 A cathode material for a lithium secondary battery characterized by being O2. Claim 8 A method for manufacturing a cathode material for a lithium secondary battery, comprising: a step of mixing an NCM-based cathode active material and a yttrium borate (YBO3) additive; and a step of heat-treating the mixture of the NCM-based cathode active material and the yttrium borate (YBO3) additive; wherein the yttrium borate (YBO3) additive comprises 1.0 to 3.0 mol% with respect to 100 mol% of the cathode material, and the particle hardness of the cathode material increases as the content of the yttrium borate (YBO3) additive increases. Claim 9 delete Claim 10 A method for manufacturing a cathode material for a lithium secondary battery according to claim 8, characterized in that as the content of the yttrium borate (YBO3) additive increases, the amount of residual Li2CO3 decreases, the change in internal pressure (ΔP) decreases, and the exothermic peak decreases. Claim 11 delete Claim 12 A lithium secondary battery comprising a positive electrode; a negative electrode; and an electrolyte layer disposed between the positive electrode and the negative electrode, wherein the positive electrode comprises a positive electrode material according to any one of claims 1 to 3, 5 and 7. Claim 13 In Clause 12, the above anode surface has Li x B y O z A lithium secondary battery characterized by having a base cathode-electrolyte interphase (CEI) layer formed. Claim 14 A lithium secondary battery according to claim 12, characterized by a long-term cycling retention rate of 95.0% or higher.

Citation Information

Patent Citations

  • Boron-yttrium composite coated high-nickel positive electrode material and preparation method thereof

    CN112397700A